Measurement of Appreciation of Clothes of University’s Students (Journal Of Educational and Psychological Researches, 2022)
Clothes are considered a means of aesthetic and artistic expression that help to hide the flaws of the body and highlight its merits , it has importance in people's lives as it reflects the individual's idea of himself and his personality. Whereas  the appreciation  in clothing  is a reflection of a person's sense of artistic components and the application of this sense to the clothes of his choice. Regarding the differences in clothing tastes by the university students according to the following variables (gender, specialization, stage of study,  age, monthly income), the current research is considered quantitative descriptive research that is concerned with studying a phenomenon that exists in reality, measuring it and analyzing its data to extract results and generalize them ,The research sample consists of (150) male and female students of different scientific and humanities at University of Baghdad, who  were randomly selected, and the research tool consisted of (47) items, which included the following dimensions (modesty, adornment, keeping pace with fashion, attracting attention, belonging to the group, self-realization).The items are organized in the form of a questionnaire . The search results showed the following: The concentration of the highest percentage of the sample in the two levels (medium, low), which indicates that the students of the university have a weak taste in clothing, also there are statistically significant differences according to research variables ,gender in favor of females in the dimension,   age in favor of age (21 years - less than 24 years) in dimension (attract attention), age (24 years - less than 28 years) in dimension (belonging to the group).  There are no statistically significant differences according to the variables, specialization, stage of study, and the  monthly income. In the dimensions of clothing tasting measure, the research came out with a set of recommendations and suggestions.